PENGARUH KONFLIK, PENGEMBANGAN KARIER, DAN STRES KERJA TERHADAP KEPUASAN KERJA GURU DAN KARYAWAN - Dyah Ayu Palupi; Mardanung Patmo Cahjono (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research aims to analyze the influence of Conflict, Career Development, and Job Stress on Teachers and Employee Job Satisfaction. The population in this study were 30 teachers and employees of SMK KRISTEN II Klaten, sampling using the census method, which is a method that uses one population group as a whole sample. The sample used in this study were 30 teachers and employees. Data collecting using a questionnaire. Data analysis was performed by testing multiple linear regression analysis with SPSS 16.00 software. The results showed that Conflict had no significant effect on job satisfaction, Career Development had a significant effect on Job Satisfaction, Job Stress had no significant effect on Job Satisfaction, and Conflict, Career Development, and Influential Job Stress simultaneous and significant for Job Satisfaction.